Atenção psicossocial em territórios raciais ancestralizados no Ceará: textualidade, narrativas e experiências em uma avaliação de(s)colonial da ação pública em saúde mental - Lima, Francisco Anderson Carvalho de (2024)
Modernity registers forms of domination circumscribed in a colonial text that updates violence in racial territories, which appear in conditions of vulnerability operated in the regime of sociability. This inscription founds a colonial trauma, unfolded as a Brazilian cultural neurosis in the operation of racism, calling for a particular organization of psychosocial care. This thesis is based on the need to unveil and overcome the dynamics of the mobilization of coloniality and raciality within the black Atlantic. The aim was to evaluate public action in mental health in the context of the development of psychosocial care in the state of Ceará from the perspective of the black Atlantic, in order to identify the institutional dynamics of public action in ancestralized racial territories. By making an analytical interlocution with the fields of Collective Health and Public Policy Evaluation, a decolonial option was made to territorialize the public experience of psychosocial care. It is implicated evaluative research, which includes the broadening of institutionality, under a post-constructivist approach to the evaluation of public policies, in fruitful dialogue with the anthropological approach and the Afro-descendant research methodology, which consider the articulation between narrative and experience. During the period from November 2021 to December 2023, management instruments were analyzed, participant observation, ethnographic incursions, workshops and in-depth interviews were carried out with 42 managers, professionals and users of psychosocial care services in the municipalities of Crato, Juazeiro do Norte, Pacajus, Horizonte and Caucaia. The technical-assistance aspects of the content of mental health and psychosocial care policies and programs were captured. The institutional trajectory of the mental health and psychosocial care policy was then constituted with a description of the public experience, investigating the institutional dynamics that contingent public action in the shaping of policies, programs and services with the announcement of the production of subjectivities and ways of life, modulated in different operations in the processes of implementing psychosocial care. Evaluative dimensions about public action in mental health emerged around narratives, territory and experiences with an anti-asylum movement in the Cariri region of Ceará, the phenomenon of public helplessness and experiences of care with black quilombola women and racial self-perception and clinical mobilization of health professionals. From this, it was possible to observe that public action unfolds colonial elements in the management, formulation and implementation regimes that include a colonial code inscribed in the daily lives of ancestral racial communities and territories. Although the inscription of the territory is recognized in the body that accesses the clinic, the operationalization of the racial scene takes place through analogy or invisibility, engendering elements of anti-blackness. As a result, there is an invisible space between the outlining of public policy and the emancipation of black and ancestral communities, constituting relevant points for the possibility of building quilombist psychosocial care.